Методологічні проблеми дослідження добросовісності (bona fides) у римському праві - Шаркова, І.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Статья посвящена проблеме методологических основ исследования концепции добросовестности.
Современная концепция добросовестности берет свое начало из максим и других правовых правил римского права. Специальное внимание уделяется проблеме толкования содержания концепции добросовестности и ее основных категорий. The article deals with issues of a problem of methodological foundation of the good faith (bona fides) concept. The modern concept of bona fides is a fundamental principle derived from the Roman law maxims and other legal rules. The special attention is given to problem of interpretation of the concept of bona fides and its basic categories.